2000
DOI: 10.1097/00005373-200001000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Medical Care Solicitation by Criminals with Gunshot Wound Injuries: A Survey of Washington, DC, Jail Detainees

Abstract: Among these "criminals," the vast majority reported that they obtained professional care for their gunshot wounds. Such evidence suggests that individuals previously thought unlikely to enter the medical care system after a firearm injury usually do so. Statistics on medically treated nonfatal gunshot wounds probably do not substantially underestimate the actual number of nonfatal shootings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…For example, a study of Washington, DC detainees found that 92% reported going to the hospital when they were shot. 8 However, that study involved only one urban area, with a sample of fewer than 100 detainees who had been shot. The present article extends that study to five additional locations throughout the US.…”
mentioning
confidence: 99%
“…For example, a study of Washington, DC detainees found that 92% reported going to the hospital when they were shot. 8 However, that study involved only one urban area, with a sample of fewer than 100 detainees who had been shot. The present article extends that study to five additional locations throughout the US.…”
mentioning
confidence: 99%
“…Furthermore, the vast majority of individuals who initially survive a gunshot wound seek medical care for their injury. This is evident even among criminals who are very likely to enter the medical care system after a firearm injury (May, Hemenway, Oen, & Pitts, 2000). Therefore, the number of shootings that were not found in the public safety or medical system records that we used was negligible and, in fact, most were able to be identified within a very short period of time.…”
Section: Methodsmentioning
confidence: 99%
“…To inform our empirical analysis, we appeal to a theoretical model of self-employment and entrepreneurship similar to Kihlstrom and Laffont (1979), where the choice to start a firm is a function of an individual’s degree of risk aversion. As ex-incarcerees/convicts presumably made choices—the commission of a crime—that increased the relative risk of losing of their valuable freedom (Abrams & Rohlfs, 2011), and/or life (May, Hemenway, Oen, & Pitts, 2000), it suggests that they are less risk averse and more willing to engage gambles and lotteries relative to individuals who have never been incarcerated/convicted for a crime. Viewing the decision to be a self-employed entrepreneur as a gamble or lottery with stochastic payoffs, the optimal choice of an individual to be self-employed can be sensitive to the degree of individual risk aversion (Cramer et al, 2002) as evidenced by Fairlie and Holleran (2012) and Hvide and Panos (2014) for individuals in general, and for illicit drug dealers in particular (Fairlie, 2002) suggests that criminals are relatively less risk averse, and perhaps relatively well-suited for entrepreneurship (Levine & Rubinstein, 2017).…”
Section: Self-employment Ex-incarceree/convict Status and Risk Avermentioning
confidence: 99%